An energy-harvesting dosimeter for iPhones - Chan, Liang Jin. (2013)
Smartphones are increasingly becoming an essential tool in life because of their many useful features. One of the most widely used features of a smartphone is its music player. With ease of access to a music player, people of all ages are often plugged in to their smartphones listening to music for long periods of time. However the majority do not know the danger of listening to loud music for extended periods of time. Studies have shown that many people, especially the younger people are slowly suffering hearing loss through excessive listening of loud music through earphones/headphones. Furthermore, over many years are prone to the risk of having permanent hearing loss. This is mainly due to the fact that they do not adhere to the safe noise dosage level and are unaware that they are listening to music above the safe dosage level. Therefore it is very important to make the user be aware of their noise dosage level as well as whether it exceeds the recommended safe dosage level.